2021
DOI: 10.1021/acs.est.0c08629
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Ion Depletion Impacts the Stability and Performance of Battery Electrode Deionization over Multiple Cycles

Abstract: Prussian blue hexacyanoferrate (HCF) materials, such as copper hexacyanoferrate (CuHCF) and nickel hexacyanoferrate (NiHCF), can produce higher salt removal capacities than purely capacitive materials when used as electrode materials during electrochemical water deionization due to cation intercalation into the HCF structure. One factor limiting the application of HCF materials is their decay in deionization performance over multiple cycles. By examining the performance of CuHCF and NiHCF electrodes at three d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 65 publications
2
16
0
Order By: Relevance
“…Until pH = 2.5 and 1.5, even after adsorption for 180 min, the values of C/C 0 are 47.51 and 78.40%, respectively, in the end, demonstrating a significant decrease in adsorption capacity. The reason may be that under the condition of low pH, the solution contains more H + , and due to the competitive effect, a large number of H + occupy the site where Cu 2+ binds to the CuS electrode, leading to the reduction of electric adsorption. ,, In addition, under the action of the shield effect of electric potential, the repulsion between adsorbed H + and Cu 2+ may also be the reason for this phenomenon. Generally, treatment of copper-containing wastewater via CDI works best under weak acid conditions …”
Section: Resultsmentioning
confidence: 99%
“…Until pH = 2.5 and 1.5, even after adsorption for 180 min, the values of C/C 0 are 47.51 and 78.40%, respectively, in the end, demonstrating a significant decrease in adsorption capacity. The reason may be that under the condition of low pH, the solution contains more H + , and due to the competitive effect, a large number of H + occupy the site where Cu 2+ binds to the CuS electrode, leading to the reduction of electric adsorption. ,, In addition, under the action of the shield effect of electric potential, the repulsion between adsorbed H + and Cu 2+ may also be the reason for this phenomenon. Generally, treatment of copper-containing wastewater via CDI works best under weak acid conditions …”
Section: Resultsmentioning
confidence: 99%
“…It was reported that excess Ni ions in solution help stabilize the Prussian blue structure, preventing Ni dissolution that results in leaching of the redox-active Fe from NiHCF. 42 NiHCF has worse rate capabilities in methanol than aqueous solutions presumably due to the reduced hydrogen bonding network. 43 After studying different cycling currents, keeping the C rate as low as possible during cycling in methanol proved to be essential for maintaining the capacity of NiHCF.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…When undergoing reduction in methanol, NiHCF had more severe dissolution. It was reported that excess Ni ions in solution help stabilize the Prussian blue structure, preventing Ni dissolution that results in leaching of the redox-active Fe from NiHCF . Therefore, we added 20 mM NiNO 3 into the methanol solution, which improved the cycling performance.…”
Section: Resultsmentioning
confidence: 99%
“…Electrochemical deionization technologies, such as capacitive deionization (CDI) and battery deionization (BDI), have been examined for deionization and nutrient recovery applications due to their good performance in selective removal of ions with low energy consumption and high thermodynamic energy efficiencies. In CDI, ions are stored in the electrical double layer (EDL) on the surfaces of capacitive electrodes byan electric field . In BDI using battery-type electrodes, for example, Prussian blue analogues (PBA), cations are intercalated into the crystal structures of PBA by faradaic processes with optima at certain electrode potentials. , The performance of both CDI and BDI systems can be impacted by various operating conditions, such as charge–discharge modes, charge–discharge rates, feed solution flow rate, feed solution concentrations, and solution pH . However, the thermodynamic and kinetic properties of cation intercalation/deintercalation for PBA electrodes used in BDI applications are relatively unexplored.…”
Section: Introductionmentioning
confidence: 99%